2010
DOI: 10.1074/jbc.m109.096842
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Heteromerization and Phosphorylation of Ligand-activated Plant Transmembrane Receptors and Their Associated Kinase BAK1

Abstract: In plants leucine-rich repeat receptor kinases (LRR-RKs) located at the plasma membrane play a pivotal role in the perception of extracellular signals. For two of these LRR-RKs, the brassinosteroid receptor BRI1 and the flagellin receptor FLS2, interaction with the LRR receptor-like kinase BAK1 (BRI1-associated receptor kinase 1) was shown to be required for signal transduction. Here we report that FLS2⅐BAK1 heteromerization occurs almost instantaneously after perception of the ligand, the flagellin-derived pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
428
1
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 422 publications
(454 citation statements)
references
References 47 publications
17
428
1
8
Order By: Relevance
“…Previous studies showed that AtPep1 binding induced PEPR1-BAK1 heteromerization [23,24]. However, in vitro reconstitution of an AtPep1-induced complex using purified proteins has not yet been reported.…”
Section: Reconstitution Of the Pepr1lrr-atpep1 And Pepr1l-rr-atpep1-bmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies showed that AtPep1 binding induced PEPR1-BAK1 heteromerization [23,24]. However, in vitro reconstitution of an AtPep1-induced complex using purified proteins has not yet been reported.…”
Section: Reconstitution Of the Pepr1lrr-atpep1 And Pepr1l-rr-atpep1-bmentioning
confidence: 98%
“…Ca 2+ has been shown to be important for the AtPep/ PEPR signaling [21,22]. Similar to FLS2 and EFR, PEPR1 stably associates with BAK1 in response to treatment with AtPeps [23,24]. A number of studies suggest that PEPR-mediated immune responses serve to amplify PTI signaling [25][26][27][28] via the JA/ET (jasmonic acid-ethylene) and SA (salicylic acid) pathways [25,28].…”
Section: Introductionmentioning
confidence: 99%
“…EFR and FLS2, although detecting different ligands, share all functional aspects of receptor activation and signal output. Activation of both receptors occurs according to the address-message concept, presumably involving ligand-induced, conformational changes that allow heteromerization with co-receptors such as BAK1 (18,21,39,40). Thus, for substitutions with parts of FLS2 that fully retain elf binding, one would rather expect functionality of receptor activation to be retained as well.…”
Section: Efr Ectodomain As Interaction Site For the Elf Ligands-map-mentioning
confidence: 99%
“…Upon activation with their respective ligands, FLS2, EFR, and AtPEPR1 seem to form heteromeric complexes with the co-receptor BAK1. Thus, intriguingly, BAK1 appears to function in the transmembrane signaling of plant RLKs with very different signal output programs (17)(18)(19)(20).The receptor kinase EFR from A. thaliana responds to bacterial elongation factor Tu (EF-Tu) with the induction of defense and increased resistance (14, 21). Mutant plants lacking this perception system show increased susceptibility to infection by Agrobacterium tumefaciens.…”
mentioning
confidence: 99%
See 1 more Smart Citation